The Influence of Organizational Culture, Education Level, and Compensation on Employee Job Satisfaction: Pengaruh Budaya Organisasi, Tingkat Pendidikan, dan Kompensasi Terhadap Kepuasan Kerja Karyawan - Fauzi, Mohammad Azis; Ubaidillah, Hasan (Universitas Muhammadiyah Sidoarjo, 2022)
The background of this research is the decrease in employee job satisfaction due to a mismatch of compensation obtained with what has been done. This study aims to determine the effect of organizational culture, education level, and compensation on employee job satisfaction at PT. Indonesia Post Office Surabaya This research uses quantitative research by testing the hypothesis. The analytical tool used is a questionnaire. The population in this study were 300 employees of PT. Indonesia Post Office Surabaya. The sample in this study was 75 respondents. The analytical tool in this study uses the SPSS application. The results show that (1) Organizational Culture has a significant effect on Job Satisfaction. (2) Education level has a positive and significant effect on Job Satisfaction. (3) Compensation has a positive and significant effect on job satisfaction. (4) Organizational Culture, Education Level and Compensation have a significant effect simultaneously on Job Satisfaction.